The Influence Of Human Resource Development, Organizational Culture On Teacher Performance Of SMP N 2 Sipora Tuapejat With Motivation As An Intervening - Sabelau, Rusmada Helen Putri; Heryanto, Heryanto (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to identify the influence of human resource development, organizational culture, and work motivation on teacher performance at SMP N 2 Sipora Tuapejat. The results of the study indicate that human resource development has a significant positive effect on teacher work motivation, as well as organizational culture which also has a significant positive effect on teacher work motivation. In addition, work motivation is proven to have a significant positive effect on teacher performance, and human resource development and organizational culture also have a significant positive effect on teacher performance. Furthermore, this study found that work motivation mediates the relationship between human resource development and teacher performance, as well as between organizational culture and teacher performance. Thus, increasing human resource development and a supportive organizational culture can increase work motivation, which in turn will contribute to improving teacher performance at SMP N 2 Sipora Tuapejat.